Breeding practices and mating strategies of Sheko cattle in south western Ethiopia - Taye, T.D.; Ayalew, W.; Hegde, B.P. (Elsevier, 2010)
Sheko cattle owners usually have limited control over breeding practice of their cattle. This is because they allot fractions of their time and resources in controlling breeding practices. Therefore, most often mating is natural and uncontrolled and this would result in non-descript herd structure. Smallholder farmers usually practice frequent destocking and restocking of herds; therefore, this frequent herd turnover usually makes the tracing back of the pedigree structure of the herd impractical. Cattle are kept to fulfil multiple functions and, therefore, they are often not best in any one of the traits of interest. Cattle breeds kept by smallholder farmers show appreciable genetic variation in their performance. Therefore, there is room for within breed selection of indigenous breeds to improve their performance. However, this potential of local breeds under a low input production environment is not well documented. Our study was, therefore, intended to document cattle breeding practices of Sheko cattle owners in south western Ethiopia.